Effect of Different Levels of Dietary Crude Protein on Growth Performance, Body Composition of Broiler Chicken and Low Protein Diet in Broiler Chicken - Gheisari , H.R.; Asasi, K.; Mostafa, I.; Mohsenifard, E. (International Journal of Poultry Science, 2015)
The aim of this study was to provide level of dietary protein without causing any undesired effects on growth performance and carcass quality. In this study 150 one day-old commercial broiler chicks (Ross 308) were randomly subjected to 3 equal protein regiments groups. Weight gain, total feed consumption, feed conversion ratio (FCR), carcass compositions, water holding capacity (WHC), ash, pH, tensile strength, dripping loss after thawing and organoleptic characters in each groups were analyzed at the end of rearing period (42 days). The results showed that total feed consumption and weight gain of high protein group was higher than the low and medium protein group. In low protein group, abdominal fat, leg weights, pH content and excretion nitrogen were lower than medium and high protein groups; however feed efficiency, breast muscle percent, moisture and protein percents of the carcass were higher. The level of dietary protein did not affect tensile strength, dripping loss and organoleptic properties of chicken muscles. In female chickens, WHC was better in the medium and high protein groups. Therefore, dietary protein level of broilers could be reduced by 2%.